Pathogen Challenge and Dietary Shift Alter Microbiota Composition and Activity in a Mucin-Associated in vitro Model of the Piglet Colon (MPigut-IVM) Simulating Weaning Transition - Gresse, Raphaële; Chaucheyras-Durand, Frédérique; Garrido, Juan J.; Denis, Sylvain; Jiménez-Marín, Angeles; Beaumont, Martin; Van de Wiele, Tom; Forano, Evelyne; Blanquet-Diot, Stéphanie (Frontiers in Microbiology, 2021)
Enterotoxigenic Escherichia coli (ETEC) is the principal pathogen responsible for post-weaning diarrhea in newly weaned piglets. Expansion of ETEC at weaning is thought to be the consequence of various stress factors such as transient anorexia, dietary change or increase in intestinal inflammation and permeability, but the exact mechanisms remain to be elucidated. As the use of animal experiments raise more and more ethical concerns, we used a recently developed in vitro model of piglet colonic microbiome and mucobiome, the MPigut-IVM, to evaluate the effects of a simulated weaning transition and pathogen challenge at weaning. Our data suggested that the tested factors impacted the composition and functionality of the MPigut-IVM microbiota. The simulation of weaning transition led to an increase in relative abundance of the Prevotellaceae family which was further promoted by the presence of the ETEC strain. In contrast, several beneficial families such as Bacteroidiaceae or Ruminococcaceae and gut health related short chain fatty acids like butyrate or acetate were reduced upon simulated weaning. Moreover, the incubation of MPigut-IVM filtrated effluents with porcine intestinal cell cultures showed that ETEC challenge in the in vitro model led to an increased expression of pro-inflammatory genes by the porcine cells. This study provides insights about the etiology of a dysbiotic microbiota in post-weaning piglets.